Collagen and elastic fibres in acute and chronic liver injury - Andrew Hall (Nature Portfolio, 2021)
Abstract The histological distinction between acute and chronic liver injury is a challenging aspect of liver histopathology. It is traditionally based on the interpretation of morphological changes to the extracellular matrix (ECM) at sites of hepatocyte loss using histochemical stains. Our aim was to investigate whether immunohistochemistry and multiplexing for collagen type (I & III) and elastic fibres and a modified Victoria blue method could be helpful. We studied 43 livers removed at transplantation for acute liver failure (ALF, 20 cases) or cirrhosis (23) plus 8 normal controls. In ALF the periportal ECM was normal in 2 cases, contained mainly collagen I associated with a ductular reaction in 6 cases, and delicate elastic strands in 11 cases. Periportal deposition of mainly collagen I and mature elastic fibres was observed in cirrhosis. In ALF the perisinusoidal ECM was intact in 4 cases, collapsed or condensed but of normal composition (predominantly collagen III) in 2 cases, and collapsed and condensed containing mostly collagen I in 17 cases (7 including delicate immature elastic strands). In contrast, bridging fibrous septa of cirrhosis contained abundant collagen 1 and bundles of mature elastin. We propose the use of a scale and the use of immunohistochemistry and multiplexing in additional to histochemical stains to characterise the ECM changes in acute and chronic liver injury.